2019
DOI: 10.11591/ijece.v9i6.pp4836-4844
|View full text |Cite
|
Sign up to set email alerts
|

A novel compact CPW Band-stop filter using O-DGS configuration

Abstract: <p>A novel and compact multi-band stop filter using two different structures of circular DGS and circular DGS loaded with O-DGS unit, has good selectivity and  wide upper pass band performance  with good rejection based on defected ground structure (DGS) integrating a circular ring  resonator to suppress undesired spurious bands frequency or harmonics in radio frequency and microwave circuits is proposed. An equivalent circuit model has been derived for the both structures of circular DGS and circular DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances. DGS has several advantages on the circuit [12], unwanted frequency suppression [13]- [15], bandwidth enhancement of antennas [16], [17], size compactness [18], [19], high power handling capability [20], isolation in antenna designs [21]- [23], and compensating parasitic capacitance of switching element to improve isolation [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances. DGS has several advantages on the circuit [12], unwanted frequency suppression [13]- [15], bandwidth enhancement of antennas [16], [17], size compactness [18], [19], high power handling capability [20], isolation in antenna designs [21]- [23], and compensating parasitic capacitance of switching element to improve isolation [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…This eliminates the need for via holes and, thereby, simplifies the circuit fabrication. Moreover, this allows simple connection of series as well as shunt components [16][17][18]. Another major advantage of CPW is that it exhibits lower conductor loss than microstrip lines [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Using the two sides of the ground provides additional miniaturization for structure. In both free etched area [9,10], witch here a rectangle DGS and loaded DGS [11,12], by entering the 'e' slot in etching area in the ground of CPW line, an electric and magnetic coupling can be implemented, which allows for an intelligible design of simple an miniaturized structures, such as this proposed low pass filter, and many other structures with the same procedure.…”
Section: Introductionmentioning
confidence: 99%